Sarcopenia Is Associated with High Pulse Pressure in Older Women - Hélio José Coelho Júnior; Samuel da Silva Aguiar; Ivan de Oliveira Gonçalves; Ricardo Aurélio Carvalho Sampaio; Marco Carlos Uchida; Milton Rocha Moraes; Ricardo Yukio Asano (Journal of Aging Research)
Introduction. Sarcopenia is a geriatric syndrome associated with impairment of muscle function, metabolism, and cognition in older women. Recent studies have shown a relationship between changes in muscle mass and the cardiovascular system. However, this relationship has not been fully elucidated. Methods. One hundred and thirty community-dwelling Brazilian older women (65.4 ± 6.3 years) were recruited to participate in this study. Data on body composition (via bioelectrical impedance measurements), cardiovascular parameters (using an automatic and noninvasive monitor), and muscle function (using a 3-meter gait speed test) were measured. Results. Sarcopenic older women (n=43) presented higher levels of pulse pressure (PP) (60.3 ± 2.6 mmHg) and lower muscle function (0.5 ± 0.0 m/s) compared with nonsarcopenic subjects (n=87) (53.7 ± 1.5 mmHg; 0.9 ± 0.0 m/s) (P<0.05). Linear regression analysis demonstrated a significantly negative association between skeletal muscle index (SMI) and PP levels (β=−226, P<0.05). Furthermore, sarcopenic older women showed a 3.1-fold increased risk of having higher PP levels compared with nonsarcopenic women (IC = 1.323–7.506) (P<0.05). Conclusion. Sarcopenic older women showed lower muscle function and higher cardiovascular risk due to increased PP levels compared with nonsarcopenic subjects.